Probing Strangeness Hadronization with Event-by-Event Production of Multistrange Hadrons - Acharya, S.; Adamova, D.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; et al. (AMER PHYSICAL SOC, 2025)
This Letter presents the first measurement of event-by-event fluctuations of the net number (difference between the particle and antiparticle multiplicities) of multistrange hadrons Xi(-) and (Xi) over bar (+) and its correlation with the net-kaon number using the data collected by the ALICE Collaboration in pp, p-Pb, and Pb-Pb collisions at a center-of-mass energy per nucleon pair root s(NN) = 5.02 TeV. The statistical hadronization model with a correlation over three units of rapidity between hadrons having the same and opposite strangeness content successfully describes the results. On the other hand, string-fragmentation models that mainly correlate strange hadrons with opposite strange quark content over a small rapidity range fail to describe the data.
Keywords: P-PB COLLISIONS; MULTIPLICITY DEPENDENCE; BARYON PRODUCTION; PROTON; Physics